Grazing and Recovery of Kelp Gametophytes Under Ocean Warming - Veenhof, Reina J.; Dworjanyn, Symon A.; Champion, Curtis; Coleman, Melinda Ann (Frontiers in Marine Science, 2022)
Kelp forests are economically important ecosystems that support a wealth of biodiversity but are declining globally. They are often replaced by biologically depauperate alternate stable states dominated by turfing algae. Hysteresis maintains algal turfs by inhibiting kelp recruitment, preventing the reestablishment of kelp forests. The mechanisms inhibiting kelp recruitment remain poorly understood as microscopic stages of kelp are difficult to study in situ. A potential mechanism contributing to the suppression of recruitment may be turf-facilitated grazing of kelp gametophytes, the haploid free-living reproductive life stage. Here we assess the resilience of kelp gametophytes to grazing pressure from a gastropod micrograzer commonly present in turf under current and future ocean warming scenarios. Gametophyte coverage and abundance were significantly reduced following grazing under all temperatures, however there was no significant effect of temperature on grazing rates. Once grazing pressure was removed, gametophyte abundance recovered to control levels, but the total coverage and length of gametophytes continued to decline in all treatments. Gametophytes were found to survive micrograzer ingestion and continued to grow in aggregations in the gastropod’s mucus trail and faeces, even producing sporophytes. Gametophyte survival post-ingestion may positively contribute to dispersal and sporophyte recruitment, however the lack of gametophyte recovery at elevated temperatures may counteract this effect under future ocean warming. Taken together, this study demonstrates complex interactions that take place in the turf micro-habitat of kelp gametophytes and highlights biotic factors influencing transitions between kelp forests and algal turfs.